3PC-015 Short term stability of diluted solutions of the monoclonal antibody daratumumab. (24th March 2020) - Mangoni, G; Selmin, F; Camuffo, L; Cancanelli, L; Piccoli, M; Rivano, M; Cervi, L; Cilurzo, F; Minghetti, P
Abstract : Background and importance: Monoclonal antibodies (mAb) are biotechnological products used as therapeutic agents. Because of their nature, mAb may go through a variety of chemical and physical degradation processes on handling. For this reason, extended in use conditions are not included in stability assessments prior to regulatory approval. Daratumumab, a CD38 targeting human IgG1κ mAb, is used in the treatment of multiple myeloma. After dilution in saline (0.9% sodium chloride) solution using the appropriate aseptic technique, it is reported to be physically and chemically stable for 24 hours under refrigerated conditions (2–8 °C) protected from light. 1 Aim and objectives: We conduct a study to evaluate the physicochemical stability of daratumumab diluted at clinically relevant concentrations over a 14 day period. Material and methods: Daratumumab was diluted to concentrations of 1.2 and 2.0 mg/mL in a low density polyethylene (LDPE) infusion bag in saline solution for intravenous injection. To determine changes in physicochemical properties over a 14 day period, various methods were used—that is, size exclusion chromatography-high performance liquid chromatography (SEC-HPLC), dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), turbidimetry, pH and osmolality. They were selected based on the preliminary results of a forced degradation study. 2 Results: All samples remained clear with no precipitates or particulate matter detected with the naked eye. No change in colour or turbidity was observed. The pH of both dilutions shifted from 5.5 to 5.8, while the osmolality value ranged from 296 to 313 mOsm/kg. SEC-HPLC did not show the formation of aggregates or fragmentations. The ratio between the major peak (retention time=13 min) and a minor signal (retention time=11 min) remained constant over time. No clear trend in the presence of sub-visible particles was observed by DLS. Indeed, the main peak of daratumumab was detected at about 13 nm which accounted for up to 98% and 95% for the 1.2 mg/mL and 2.4 mg/mL solutions, respectively. These results were in agreement with the NTA data. Conclusion and relevance: No physicochemical variations were evident in daratumumab solution at 1.2 mg/mL and 2 mg/mL stored in an LDPE infusion bag at 2–8°C. Evaluation of the biological activity is required to confirm the extended in use stability. References and/or acknowledgements: 1. Darzalex summary of product characteristics. https://ec.europa.eu/health/documents/community-regis- ter/2017/20170428137394/anx_137394_en.pdf 2. Joubert MK, et al. J Biol Chem 267(30): 25266–25279. No conflict of interest.